Use of residual waste glass in an alkali-activated binder – Structural characterization, environmental leaching behavior and comparison of reactivity. (February 2021) - Bouchikhi, Abdelhadi; Mamindy-Pajany, Yannick; Maherzi, Walid; Albert-Mercier, Cyrille; El-Moueden, Hamza; Benzerzour, Mahfoud; Peys, Arne; Abriak, Nor-Edine
Abstract: Waste glass based geopolymers have a high potential in the future as an eco-friendly inorganic binder. However, limited studies are available on the use of the residue of waste glass recycling in this type of binder. This work investigates the valorization of Residual Waste Glass (RWG) (the final waste of glass recycling centers) crushed at d90 < 13 μm in a geopolymer activating solution. RWG is thus used as source of free silicon with metakaolin (MK) as source of aluminosilicates. The activating solution from RWG was prepared in four ratios with a sodium hydroxide solution of 10 M: R1 (10M-NaOH + 10 g RWG), R2 (10M-NaOH + 20 g RWG), R3 (10M-NaOH + 30 g RWG) and R4 (10M-NaOH + 40 g of RWG). The effect of these treatments on the mobility of metallic and metalloid trace elements (MMTE) and major elements (Si 4+ and Al 3+ ) was measured. The structure of the solid phases produced after drying at 120 °C/24 h was studied using Fourier Transformed Infrared (FTIR) spectroscopy, Nuclear Magnetic Resonance (NMR) and XRD analyses. From these analyses, activating solution R3 was deemed optimal. The formulation of geopolymer mortars using MK and three activator sources: The optimized activating solution from RWG (R3), Commercial Sodium Silicate solution (CSS) and a reference activator formed by NaOH with RWG blended with the MK to obtain the same molar ratios in the geopolymer mixture. The mechanical and environmental performance results both highlight the interest of dissolving the RWG in NaOH first before insertion into the matrix. This study shows that treated glass R3 becomes an activating solution with good reactivity for obtaining a geopolymer binder and enhanced properties compared to the CSS source. Graphical abstract: Image 1 Highlights: Sodium silicate solution can be produced from residual waste glass and NaOH. 30 g of residual waste glass in 100 ml 10 M NaOH results in an optimal activator. Better compressive strength properties for TGMK which reaches 28 MPa at 28 days.